From Pedagogy to Digital Cultural Literacy: Examining the Correlation between Teachers’ Knowledge of Bloom’s Taxonomy, Character Education, and Digital-Based Interpretation of Javanese Philosophy - Sulton, Sulton; Hermawan, Yudan; Mahardhani, Ardhana Januar; Rusdiani, Nurtina Irsad; Wulansari, Betty Yulia; Mufanti, Restu (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to analyze the relationship between teacher’s knowledge of Bloom’s Taxonomy and character education with their digital-based understanding of the Javanese philosophy Sura Dira Jayaningrat Lebur Dening Pangastuti within technology-integrated cultural education enviroments. Methodology: A quantitative correlational method was implemented using a digital Likerts-scale questionnaire administered through an online platform. Data were analysed with SPSS using validity and reliability test, Pearson product-moment correlation, and multiple regression analysis to measure relationships among Bloon’s Taxonomy knowledge, character education knowledge, and digital-based philosophical understanding. Main Findings: The study reveals significant positive correlations between teachers’ knowledge of Bloom’s Taxonomy and their digital-based understanding of Javanese philosophy. Teachers’ knowledge of Indonesian character education also shows a strong and significant relationship. Combined, both variables explain 92,8% of the variance in teacher’s ability to interpret and internalize philosophical values within technology-supportes cultural learning. Novelty/Originality of this study: This study offers a new framework linking pedagogical knowledge with digital cultural interpretation, demonstrating how technology enhances teachers’ ability to translate Bloom’s Taxonomy and character education technology by integrating local wisdom, digital media, and oedagogical theory into a coherent model for cultural preservation.